The restaurant : from concept to operation - John R. Walker (Hoboken, NJ : Wiley, 2022)
The Restaurant: From Concept to Operation, Fifth Edition gives readers the knowledge they need to conceive, open, and run any type of restaurant, from fast-food franchise to upscale dining room.